Metamorphoses : resurrection, body, and transformative practices in early Christianity - Seim, Turid Karlsen; Økland, Jorunn (Ekstasis (Walter de Gruyter & Co.) ;, 2009)
How were ideas and experiences of transformation expressed in early Christianity and early Judaism? This volume explores the social and philosophical frameworks within which transformative ideas such as resurrection and practices of becoming "a new being" were shaped, and the analogies and parameters by which transformation was being noted and asserted. The focus on transformation helps connect topics that tend to be studied separately, such as cosmology, resurrection, aging, gender, and conversion. The textual material is wide-ranging and there are new readings of core passages.